TO THE BASICS OF MODERN POLITICAL ANTHROPOLOGY: FREEDOM AND JUSTICE IN THE SOCIAL CONTRACT THEORY OF T. HOBBES - L. A. Sytnichenko; D. V. Usov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The purpose of the study lies in critical reconstruction of Thomas Hobbes’s social contract theory as an important principle not only of modern political anthropology, but also of modern and postmodern social projects. As well as, in the unfolding of the fundamentally important both for the newest social-philosophical and philosophical-anthropological discourses of the thesis that each individual is the origin of both personal and institutional freedom and justice, making the contract first of all with himself, with his desires and sorrows and then with other people and the state. Theoretical basis. The principle of social contract offered by Hobbes became a new social, methodologically significant and relevant principle of regulation of activity, which indicates essential for the modern political philosophy and the philosophy of law transition from teleological (ancient and medieval) to legal (modern) ideas of justice. For an in-depth study of the philosophical and anthropological aspects of Hobbes’s contractualism, we used the historical-comparative and contextualization method, as well as the works of leading native and foreign researchers of Hobbes, who uphold the provisions on the organic affiliation of fundamental socio-philosophical and philosophical-anthropological questions about the nature of man, the relation of coercion, freedom and justice with the discourse of social contract. Originality. On the basis of a consistent analysis of the anthropological component of Hobbes’s theory of social contract, an in-depth understanding of modern contractualism and contemporary discussions in the field of its existential and anthropological component is offered, as well as the thesis that political anthropology is the core of the philosophical anthropology because it makes possible the methodologically important understanding of the basic problems of human existence – the interaction of justice and freedom, self-interest and public good, as well as it quite clearly outlines the ways to overcome the dilemmas of liberalism and communitarianism, individualism and holism. Conclusions. Political anthropology of T. Hobbes constructed in the context of a modern social project, justified the issue of interaction between freedom and justice, which is fundamentally important to nowadays, through the search for such a way of social relations, in which an individual, being in the realm of social existence, would seek to limit his own selfishness and freedom for the sake of the common will of the majority. Thanks to Hobbes, the idea of external humility in disobedience to the inner, of freedom of conscience as a "human and citizen", of an understanding of individual independence, which is not just a permissible but accepted by state power, has been acquired with exceptional theoretical and practical meaning. Thanks to Hobbes’s works, the essence (and the falsity of simplified interpretations of the latter’s heritage) was revealed by the relationship between the cooperative and the conflicted vision of man.